2004
DOI: 10.1177/0115426504019003226
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Response to Parenteral Nutrition in Critical Care

Abstract: Parenteral nutrition (PN) is an essential component in the support of critically ill patients with gastrointestinal dysfunction. Although PN cannot fully reverse hypermetabolism and accelerated skeletal muscle breakdown observed during periods of critical illness, it can prevent the adverse effects associated with malnutrition. The use of PN is not without complications, so care must be taken to ensure successful clinical outcomes with this complex therapy. Strategies have been developed by practitioners to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Consistent with the previous systematic reviews, 7, 8 the present one demonstrated the clinical benefits of enteral nutrition in comparison with parenteral nutrition. The mounting data evidence that, most likely, this is not because of better nutritional effect of enteral nutrition over parenteral nutrition, but rather because of the marked differences between the groups with regard to intestine function 31–33 . In its turn, it suggests that (in)adequate intestine function may be either a confounder or an effect of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous systematic reviews, 7, 8 the present one demonstrated the clinical benefits of enteral nutrition in comparison with parenteral nutrition. The mounting data evidence that, most likely, this is not because of better nutritional effect of enteral nutrition over parenteral nutrition, but rather because of the marked differences between the groups with regard to intestine function 31–33 . In its turn, it suggests that (in)adequate intestine function may be either a confounder or an effect of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…We go one step further to recommend that, as currently constituted, IV lipid emulsions be avoided in the average critically ill patient. 20 Despite the conflicting experimental evidence reviewed by Sacks, 49 there are 2 clinical studies comparing lipid-free PN to lipid-containing PN. 44,52 When aggregated, they suggest a statistically significant reduction in infectious complications associated with lipid free-PN (0.63, 95% CI 0.42-0.93; p ϭ .02).…”
Section: Optimizing the Benefits And Minimizing The Risks Of Parentermentioning
confidence: 99%